Pesticide Poisonings in Low- and Middle-Income Countries - Erik Jørs; Dinesh Neupane; Leslie London (SAGE Publishing, 2018)
Aims and scope This editorial is an introduction to the papers making up the special issue on 'pesticide poisonings in low- and middle income countries'.